Exploring the Anti-Burkholderia cepacia Complex Activity of Essential Oils: A Preliminary Analysis. (19th February 2014) - Maida, Isabel; Lo Nostro, Antonella; Pesavento, Giovanna; Barnabei, Martina; Calonico, Carmela; Perrin, Elena; Chiellini, Carolina; Fondi, Marco; Mengoni, Alessio; Maggini, Valentina; Vannacci, Alfredo; Gallo, Eugenia; et al.
Abstract : In this work we have checked the ability of the essential oils extracted from six different medicinal plants ( Eugenia caryophyllata, Origanum vulgare, Rosmarinus officinalis, Lavandula officinalis, Melaleuca alternifolia, and Thymus vulgaris ) to inhibit the growth of 18 bacterial type strains belonging to the 18 known species of the Burkholderia cepacia complex (Bcc). These bacteria are opportunistic human pathogens that can cause severe infection in immunocompromised patients, especially those affected by cystic fibrosis (CF), and are often resistant to multiple antibiotics. The analysis of the aromatograms produced by the six oils revealed that, in spite of their different chemical composition, all of them were able to contrast the growth of Bcc members. However, three of them (i.e., Eugenia caryophyllata, Origanum vulgare, and Thymus vulgaris ) were particularly active versus the Bcc strains, including those exhibiting a high degree or resistance to ciprofloxacin, one of the most used antibiotics to treat Bcc infections. These three oils are also active toward both environmental and clinical strains (isolated from CF patients), suggesting that they might be used in the future to fight B. cepacia complex infections.